Pharmacological inhibition of the ubiquitin-specific protease 8 effectively suppresses glioblastoma cell growth - Long Yu; Hu Zengchun; Yang Dian; Wang Fuqiang; Zhao Chen’ge; Zhang Yang; Zhang Yingqiu; Ma Hui; Lv Huiyi (Open Life Sciences, 2023)
Glioblastoma (GBM) is a malignant brain tumor. The purpose of this study is to estimate the potential effects and underlying mechanisms of a ubiquitin-specific protease 8 (USP8) small-molecule inhibitor on the phenotypic characteristics of GBM cells. The growth, migration, invasion, and stemness of GBM LN229 and T98G cells were evaluated by conducting cell proliferation, colony formation, wound healing, transwell, Ki-67 staining, spheroid formation, and ionizing radiation assays, and the results collectively showed the suppressive effects of USP8 inhibition on GBM cells. Furthermore, transcriptomic profiling of GBM cells treated with the USP8 inhibitor deubiquitinase (DUB)-IN-1 revealed significantly altered mRNA expression induced by pharmacological USP8 inhibition, from which we confirmed downregulated Aurora kinase A (AURKA) protein levels using immunoblotting assays. Our findings indicated that the proliferation, invasion, and stemness of LN229 and T98G cells were markedly suppressed by USP8 inhibition. Pharmacological USP8 suppression elicits multiple tumor-inhibitory effects, likely through dysregulating various mRNA expression events, including that of the key cell cycle regulator and oncogenic protein AURKA. Therefore, our observations corroborate the GBM-supportive roles of USP8 and suggest pharmacological USP8 inhibition is a viable therapeutic approach to target GBM. The purpose of this study was to investigate the effect and mechanism of action of the USP8 inhibitor DUB-IN-1 on GBM.